(untitled) (The Gaze: Journal of Tourism and Hospitality, 2016)
Hospitality organizations face a serious threat from disasters, with only few of these firms engaged in planning for effective disaster management. Nepal has a high risk profile for natural disasters; and it was struck by the great earthquake on April 25th, 2015 which was followed by 400-plus aftershocks creating havoc mostly in the eastern, central and western part of the country. This article aims to present some insight on the impact of the earthquake in the hospitality sector. Secondary data available from various reports, newspaper articles, government reports, and studies conducted by individuals and different organizations have been taken into account while preparing this article. Some people associated with hotels of different category from different locations were also interviewed to get in-depth views on the effects of the natural calamity. The damages and losses caused by the earthquake have engulfed most of the tourism-related organizations and activities. This has subsequently made the concerned stakeholders – regardless of their size and scope of operation – to rethink about their strategy for disaster preparedness. After studying the extent of the same, all hospitality firms are encouraged to prioritize the need and to engage in practice for disaster and crisis management. The Gaze: Journal of Tourism and Hospitality Vol.7 2015 pp.87-115